Health monitoring of repaired composite structure using MXene sensor. (October 2021) - Wang, Xiaoqiang; Lu, Jian; Lu, Shaowei; Li, Bo; Zhang, Lu; Ma, Chengkun; Ma, Keming; Lin, Lunyang; Jiang, Xiaowei; Yang, Bin
Abstract: With the wide application of composite materials in aviation structures, the research on the repair methods of composite materials is getting deeper and deeper. However, due to the particularity of composite materials, it is difficult to visually observe the repair effect and service state of the composite repair structure, which requires a high sensitivity piezoresistive strain sensor. A novel MXene film sensor technology which can provide real time and in situ structure health monitoring of composite structures was proposed in this work. MXene thin films with excellent properties can be obtained by the preparation method proposed in this paper. MXene sensors are fabricated and arranged in arrays on the composite repair structure to monitor strain at different locations on the composite repair structure. The piezoresistive response of MXene sensor is obtained and the main working mechanism of MXene is explained. The array distribution of MXene sensors in the repaired structure provides a more effective and complete monitoring process for further understanding the failure mechanism of the repaired structure. The proposed monitoring method based on MXene sensor is suitable for studying the health monitoring of composite repair structures under tensile and compression conditions. Graphical abstract: Image 1 Highlights: The MXene sensor film can be made in a simple way, which can be easily co-cured with the composite material. resin can also be used as a matrix for pressure transmission, so that the pressure can be transmitted to the MXene sensor for monitoring. The damage mechanism of the composite repair structure can be analyzed through the sensor resistance responses of the composite repair structure under different stress states. The array distribution of MXene sensors in the repaired structure provides a more effective and complete monitoring process for further understanding the failure mechanism of the repaired structure. The introduction of FPC can protect the sensor from damage to a certain extent. In addition, it can reduce wiring problems caused by multiple sensors.